Achieving Differential Privacy in Smart Home Scenarios - Vidal, Israel C.; Rousseau, Franck; Machado, Javam C. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2019)
With the growth of the Internet of Things (IoT) and Smart Homes, there is an ever-growing amount of data coming from within people’s houses. These data are intrinsically private and should be treated carefully, despite their high value for analysis. In this work, we propose a differentially private strategy to estimate frequencies of values in the context of Smart Home data.